Omics disciplines in food science - Ramírez-Navas, Juan Sebastián; Jaramillo-López , Fressia; López-Parra, Lizbeth Lorena (Revista Colombiana de Investigaciones Agroindustriales, 2023)
The omics sciences comprise a group of scientific disciplines that systematically and comprehensively investigate the biological and biochemical processes occurring in organisms or biological systems. This narrative review focuses on the omics disciplines (genomics, transcriptomics, proteomics, and metabolomics) as well as their subdisciplines (such as nutrigenomics, nutrigenetics, epigenomics, among other) within the field of foodomics. The objective is to present the applications of these disciplines in food sciences and to elucidate their individual scopes. o achieves this, a search was conducted using Boolean operators and search equations that combined omics and food science-related keywords across various databases. Relevant articles meeting the inclusion criteria were selected. The findings demonstrate that Foodomics is the omics science most closely related to Food Science. Foodomics explores the molecular processes of food production and transformation, while also examining the impact of food consumption on human health. Additionally, this interdisciplinary science has found practical applications in improving nutrient content in plants with a high potential for addressing health concerns. It is concluded that the action of omic sciences in food science is little known and applied, however, it has a very broad potential for action.